Endophytic fungi: hidden treasure chest of antimicrobial metabolites interrelationship of endophytes and metabolites - Jha, Priyanka; Kaur, Tamanna; Chhabra, Ishita; Panja, Avirup; Paul, Sushreeta; Kumar, Vijay; Malik, Tabarak (Frontiers in Microbiology, 2023)
Endophytic fungi comprise host-associated fungal communities which thrive within the tissues of host plants and produce a diverse range of secondary metabolites with various bioactive attributes. The metabolites such as phenols, polyketides, saponins, alkaloids help to mitigate biotic and abiotic stresses, fight against pathogen attacks and enhance the plant immune system. We present an overview of the association of endophytic fungal communities with a plant host and discuss molecular mechanisms induced during their symbiotic interaction. The overview focuses on the secondary metabolites (especially those of terpenoid nature) secreted by endophytic fungi and their respective function. The recent advancement in multi-omics approaches paved the way for identification of these metabolites and their characterization via comparative analysis of extensive omics datasets. This study also elaborates on the role of diverse endophytic fungi associated with key agricultural crops and hence important for sustainability of agriculture.